Mycotic Quality and Potential Health Implications of Selected Pharmaceutical Syrup Sold in Minna, Niger State, Nigeria - Abah , D. O.; Bala, J. D.; Garba , D. E.; Jesse , I. A.; Sadiku , J. O.; Ikegima , E.; Attah, F. (Researchers Journal of Science and Technology, 2024)
Syrups are liquid medications that contain active ingredients and are ideal for babies, children, and the elderly due to their ease of use. However, their high sugar content and other additives used to enhance taste and stability in syrups make them especially susceptible to microbial growth. This study is aimed at evaluating the mycotic quality of four types of syrup - Vitamin C, Paracetamol, Cough, and Multivitamins sourced from three pharmaceutical stores through spread plate methods. Fungal counts in the samples ranged from 1 x 10¹ to 4 x 10¹ CFU/mL. Mycological analysis identified fungal species including Aspergillus niger, Trichophyton megninii, Penicillium notatum, Aspergillus fumigatus, and Mucorpusillus, with Aspergillus niger and Trichophyton megninii being the most frequently detected followed by mucorpusllus and Peniciliun notatum. The mycotic load met the European Pharmacopoeia’s fungal limit of ≤10¹ CFU/mL. The results emphasize the importance of rigorous quality control in pharmaceutical production and storage to prevent microbial contamination and protect patient health. Therefore, it is imperative to promote public awareness campaigns regarding the proper storage of pharmaceutical syrups.